Mind Mapping Learning Model in “Manusia Bertuhan”: A Quasi-Experimental Study on Cognitive and Affective Integration: (Model Pembelajaran Mind Mapping dalam “Manusia Bertuhan”: Sebuah Studi Kuasi-Eksperimental tentang Integrasi Kognitif dan Afektif) - Ushwa Dwi Masrurah Arifin Bando; Hasnidar Hasnidar (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
Higher education Islamic Religious Education plays a strategic role in shaping students who not only understand Islamic teachings conceptually but also internalize spiritual values in their daily lives. However, learning practices in universities often emphasize cognitive understanding rather than the integration of cognitive and affective dimensions. This study aims to analyze the implementation of mind mapping in the “Manusia Bertuhan” (Human as a Theistic Being) learning material to integrate students’ cognitive understanding and spiritual awareness in the Management Study Program, Faculty of Economics and Business, Universitas Negeri Makassar, Indonesia. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest model. The participants consisted of 38 management students enrolled in the Islamic Religious Education course in the 2025/2026 academic year, selected through purposive sampling. Data were collected through cognitive tests, a spiritual awareness questionnaire using a Likert scale, observation sheets of student engagement, and assessment rubrics for mind mapping products. Data analysis included descriptive statistics, normality testing, paired sample t-test, normalized gain (N-gain), correlation analysis, and effect size calculation (Cohen’s d) using SPSS. The findings revealed significant improvements in both cognitive and affective domains after the implementation of mind mapping. The mean cognitive score increased from 67.4 to 82.6, while spiritual awareness scores increased from 72.1 to 85.3. The paired sample t-test showed a significant difference (p < 0.001) with a large effect size (Cohen’s d = 0.87). In addition, correlation analysis indicated a positive relationship between cognitive understanding and spiritual awareness (r = 0.61, p < 0.01). These results suggest that mind mapping effectively supports the integration of knowledge and value internalization in Islamic Religious Education learning. The study implies that visual and student-centered learning strategies can strengthen both conceptual understanding and spiritual development of university students. Future studies may expand the design using control groups and broader academic contexts.